The Motivations for the Adoption of Management Innovation by Local Governments and its Performance Effects. (24th May 2021) - Andrews, Rhys; Bellò, Benedetta; Downe, James; Martin, Steve; Walker, Richard M.
Abstract: This article analyses the economic, political, and institutional antecedents and performance effects of the adoption of shared Senior Management Teams (SMTs)—a management innovation (MI) that occurs when a team of senior managers oversees two or more public organizations. Findings from statistical analysis of 201 English local governments and interviews with organizational leaders reveal that shared SMTs are adopted to develop organizational capacity in resource‐challenged, politically risk‐averse governments, and in response to coercive and mimetic institutional pressures. Importantly, sharing SMTs may reduce rather than enhance efficiency and effectiveness due to redundancy costs and the political transaction costs associated with diverting resources away from a high‐performing partner to support their lower‐performing counterpart.